2013
DOI: 10.1016/j.engfracmech.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behaviour of notched round bars made of PMMA subjected to torsion at −60°C

Abstract: This paper presents seventy new experimental results from PMMA notched specimens tested under torsion at -60 °C. The notch root radius ranges from 0.025 to 7.0 mm. At this temperature the non-linear effects previously observed on specimens of the same material tested at room temperature strongly reduce.The averaged value of the strain energy density over a control volume is used to assess the critical loads to failure. The radius of the control volume and the critical strain energy density are evaluated a prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…One possible reason for this shortcoming can be related to the difficulties that exist for testing the cracked sample under pure mode III. A review of literature shows that some limited specimens including the bar containing either circumferential crack or V and U notches subjected to torsion [25][26][27][28][29], the inclined cracked compact tension specimen [30,31], the inclined edge cracked bend beam [32] and the new edge cracked plate test configuration loaded by a special pin loading fixture which has been suggested recently by Ayatollahi and Saboori [33] are only able to produce the out of-plane deformation in the flanks of a crack. However, in practice the influence of other deformation modes (i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…One possible reason for this shortcoming can be related to the difficulties that exist for testing the cracked sample under pure mode III. A review of literature shows that some limited specimens including the bar containing either circumferential crack or V and U notches subjected to torsion [25][26][27][28][29], the inclined cracked compact tension specimen [30,31], the inclined edge cracked bend beam [32] and the new edge cracked plate test configuration loaded by a special pin loading fixture which has been suggested recently by Ayatollahi and Saboori [33] are only able to produce the out of-plane deformation in the flanks of a crack. However, in practice the influence of other deformation modes (i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…For example, the following publications can be quoted under (i) pure mode I loading [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]; (ii) mixed mode I/II loading ; (iii) pure mode II loading [39][40][41]; and (iv) mode III and mixed mode I/III loadings [42][43][44]. Most of the investigations carried out in the context of brittle fracture of notched components have been quoted in two valuable review papers [45,46].…”
Section: Introductionmentioning
confidence: 98%
“…Taking the results of Berto et al (2012Berto et al ( , 2013 together it is observed that the overall fracture surface in cracked or notched rods that fail in a brittle manner can transition from a spiral to a flat but faceted surface as the level of tension to torsion increases and as the notch becomes sharper, concentrating load at the notch root. In the present work we further explore this transition by mapping out the spiral and flat fracture regimes for circumferentially notched PMMA rods with varying notch depth.…”
mentioning
confidence: 95%
“…The transition point is not determined nor is the impact of different notch depths explored. In studies of failure under tension and shear Berto et al (2012Berto et al ( , 2013 tested PMMA rods with U and V shaped notches and varying notch depths and root radii. They observe that for a given notch depth the fracture surface transitions from spiral to flat as the notch root radius decreases.…”
mentioning
confidence: 99%